Profil Keterampilan Berpikir Kritis dan Perilaku Mahasiswa Pendidikan Fisika - Heni Safitri; Ida Hamidah; Wawan Setiawan; Ida Kaniawati (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2021)
Article presents critical thinking skills of in-service physics teachers (IPTs) and their behavior in online. This research is a survey that describes the profile of IPTs critical thinking skills and their behavior in online learning. This survey involved 46 IPTs of four semester at Open University in Indonesia. Data related to IPTs’ critical thinking were collected through the General Critical Thinking Test by Lauren Starkey, while the data related to IPTs’ critical thinking skills were collected through tests of critical thinking skills. Data were analyzed by using quantitative descriptive technique. Based on the results of the data analysis, it was concluded that generally the IPTs’ critical thinking skills can be categorized dominated as low, while their behavior in online learning dominated only read and view the activities. The result of critical thinking skills and their behavior in online learning will be used as a reference in developing a problem based learning in the online physics learning context.